Inverted Lymphoglandular Polyp in Descending Colon. (12th February 2015) - Zhou, Shengmei; Ma, Yanling; Chandrasoma, Parakrama
Abstract : A 47-year-old male with a history of left colon cancer, status post left colon resection for 12 years, presented with rectal bleeding. Colonoscopic examination revealed an 8 mm sessile polyp in the proximal descending colon. Microscopic examination showed that the surface of this polyp was covered with a layer of normal colonic mucosa with focal surface erosion. In the submucosal layer, an intimate admixture of multiple cystically dilated glands and prominent lymphoid aggregates with germinal centers was seen. The glands were lined by columnar epithelium. Immunohistochemical staining showed the glands were positive for CK20 and CDX2 and negative for CK7, with a low proliferative index, mostly consistent with reactive colonic glands. The patient remained asymptomatic after one-year follow-up. A review of the literature shows very rare descriptions of similar lesions, but none fits exactly this pattern. We would designate this inverted lymphoglandular polyp and present this case to raise the awareness of recognizing this unusual histological entity.